Eksperimentasi Model Pembelajaran Blended Learning menggunakan OpenLearning dan Classrom Lesson Ditinjau dari Motivasi Belajar Terhadap Hasil Belajar Mahasiswa - Guntur Nurcahyanto (Jurnal Penelitian Sains Teknologi, 2025)
Blended learning is a combination of different learning environments such as face-to-face learning (classroom lesson) with computer-based learning medium in the classroom combined with e-learning learning using the OpenLearning of Learning Management System (LMS) media compared to distance learning (virtual). This study aims to determine the effect of learning with the blended learning model in terms of learning motivation on student learning outcomes in the biology education study program of FKIP UMS. The type of this research is quasi-experimental quantitative research. The results of the study include: a) There is an effect of using Blended Learning with E-learning learning models on student learning outcomes; and b). There is an influence of strong, medium, and low learning motivation on student learning outcomes. It was concluded that learning the Blended Learning model by combining LMS OpenLearning and classroom lessons has an impact on increasing student motivation and learning outcomes.